Improving survival in patients with trisomy 18. Issue 4 (8th December 2021) - Tamaki, Shoko; Iwatani, Sota; Izumi, Ayako; Hirayama, Kentaro; Kataoka, Dai; Ohyama, Shohei; Ikuta, Toshihiko; Takeoka, Emiko; Matsui, Sachiko; Mimura, Hitomi; Minamikawa, Shogo; Nakagishi, Yasuo; et al.
Abstract: The effects of medical and surgical interventions on the survival of patients with trisomy 18 have been reported, leading to changes in perinatal management and decision‐making. However, few studies have fully reported the recent changes in survival and treatment of trisomy 18. We examined how treatment and survival of patients with trisomy 18 have changed over a decade in a Japanese pediatric tertiary referral center. This retrospective cohort study included patients with trisomy 18 who were admitted within the first 7 days of life at the Hyogo Prefectural Kobe Children's Hospital between 2008 and 2017. The patients were divided into early period (EP) and late period (LP) groups based on the birth year of 2008–2012 and 2013–2017, respectively. Changes in treatment and survival rates were compared between the two groups. A total of 56 patients were studied (29 in the EP group and 27 in the LP group). One‐year survival rates were 34.5% and 59.3% in the EP and LP groups, respectively. The survival to discharge rate significantly increased from 27.6% in the EP group to 81.5% in the LP group ( p < 0.001). The proportion of patients receiving surgery, especially for congenital heart defects, significantly increased from 59% in the EP group to 96% in the LP group ( p = 0.001). In our single‐center study, survival and survival to discharge were significantly improved in patients with trisomy 18, probably because of increased rate of surgical interventions. These findings may facilitate better decision‐making by patients' families and healthcare providers.